Urgensi Supervisi Akademik sebagai Fundamen Profesionalisme Guru - Ayuni, Rina; Mutohar, Prim Masrokan; Maunah, Binti (Universitas Muhammadiyah Surabaya, 2024)
Teachers have a very vital role in the world of education so teacher professionalism is needed to achieve educational goals. The problem that often occurs now is that many teachers are not updated with the latest developments in education. This indicates that teacher professionalism has begun to decline. One of the objectives of supervision is to improve the professional abilities of teachers so that the quality of teaching and learning situations can be improved. This research aims to understand the urgency of academic supervision, to determine the form of teacher professionalism and to determine the urgency of academic supervision as a foundation of teacher professionalism. The method used in this research is literature study. This research was conducted in September-December 2023. Based on the results of the analysis, there are several principles that supervisors must pay attention to and realize in carrying out academic supervision. There are four competencies that teachers must have, and there are several teacher development techniques that can be carried out by a supervisor. in increasing the professionalism of teachers in schools. Keywords : supervision, professionalism, teacher